MULTI-SEGMENTED FOOT LANDING KINEMATICS IN SUBJECTS WITH CHRONIC ANKLE INSTABILITY. Issue 7 (11th March 2014) - De Ridder, R; Willems, T; Vanrenterghem, J; Robinson, M; Palmans, T; Roosen, P
Abstract : Background: Chronic ankle instability (CAI) is associated with inadequate control during landing tasks. Joint kinematics have been shown influential in the capacity to accommodate for the incurred high loading. Objective: The purpose of this study was to evaluate whether multi-segmented foot kinematics of the impact phase of landing tasks can reveal further control issues in subjects with CAI, copers, and controls. Design: Case-control design. Setting: All subjects were evaluated in a laboratory setting with a 3D kinematic setup. Participants: 96 recreationally active subjects (38 subjects with CAI, 28 copers and 30 controls) were included in the study. Risk factor assessment: All subjects performed a vertical drop and side jump landing task. Data were collected using a force plate and a 6-camera opto-electronic system. Main outcome measurements: Foot and ankle kinematics were registered using a rigid foot model and the six-segment Ghent Foot Model (GFM), along with vertical ground reaction forces. Group differences were evaluated using Statistical Parametric Mapping and ANOVA with post-hoc Bonferroni correction. Results: In general, similar sagittal plane differences were found for vertical drop and side jump. Subjects with CAI and copers exhibited less plantar flexion at touch down. In addition, unlike the coper group, the CAI group demonstrated a stiffer landing pattern (smaller ROM) compared to the control group, leading to higher loading rates. Furthermore, subjects with CAI had a more inverted midfoot position compared to controls during side jump and more midfoot in/eversion ROM than copers during vertical drop. Copers exhibited less plantarflexion/dorsiflexion ROM in the lateral and medial forefoot for both conditions. Conclusions: Subjects with CAI displayed an altered, stiffer kinematic landing strategy and related alterations in landing kinetics, which might predispose them for episodes of giving way and actual ankle sprain events.